'If it's not worth doing half-assed, then it's not worth doing at all': Police views as to why new strategy implementation fails. (3rd March 2020) - Kalyal, Hina; Huey, Laura; Blaskovits, Brittany; Bennell, Craig
ABSTRACT: Strategy implementation is the most challenging aspect of strategic management. In the case of police organizations, failure to effectively carry out a strategy results in loss of organizational resources and employee commitment. The present study is an attempt to explore the reasons behind failure of new strategies by drawing upon qualitative survey responses from 353 police officers and civilian employees from seven agencies across Canada. The results reflect mostly negative sentiments towards strategy implementation efforts, with failure attributed to issues ranging from leadership incompetence to lack of organizational resources. These concerns must be taken into account by police leaders in order to address challenges associated with strategy implementation in their organizations.